Dinamika Kerjasama Indonesia dengan United Nations Office on Drugs and Crime (UNODC) Pada Kasus Narkoba Dalam Perspektif Liberalisme Institusionalis - Syifa Kinanthi Puji Utami; Rahmi Fitriyanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
Drugs are a type of transnational organized crime that leads to violence and health problems. All aspects of social life are significantly affected by the rise of drug crime, including in Indonesia. Therefore, Indonesia cooperates with the United Nations Office on Drugs and Crime (UNODC). With the theory of liberal institutionalism, this article aims to analyze the perspectives on the cooperation between the two. It is found that the cooperation between Indonesia and UNODC uses the principle of the rule of law as well as the principles of cooperation and interdependence. The research also found challenges that are still found in this cooperation.